Hold me responsible: The role of corporate social responsibility and corporate reputation for client-perceived value. (3rd April 2017) - Arslanagic-Kalajdzic, Maja; Zabkar, Vesna
Abstract : Purpose: Corporate communication practices are becoming ever more important for business service clients, as they signal quality and hence are related to client-perceived value. The purpose of this paper is to examine the interplay between corporate social responsibility (CSR), corporate reputation and client-perceived value, and to assess the moderating role of strategic orientation in business service relationships. Design/methodology/approach: The conceptual framework based on the corporate communication framework, signaling theory and relationship marketing theory has been tested on a survey sample of 228 client firms, using covariance-based SEM and additional procedures for assessment of mediation and moderated mediation. Findings: This paper reveals that communication practices concerning CSR positively and significantly influence client-perceived value. The authors show that reputation fully mediates the effect of CSR on client-perceived value. Finally, the effect of CSR on value is stronger if the client firm has a short-term strategic orientation, while long-term strategic orientation boosts the effect of corporate reputation on customer-perceived value. Research limitations/implications: Further research on the topic may involve developing links between other elements of the corporate communication framework and client-perceived value. Originality/value: The originality of the paper lies in better understanding the effects of CSR and corporate reputation on client-perceived value. The authors provide empirical evidence of the mediating role of reputation between the CSR (seen as "actions") and client-perceived value.